2006
DOI: 10.1159/000092676
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Syndromes in Children and Adolescents after Road Traffic Accidents – A Prospective Cohort Study

Abstract: Background: The impact of road traffic accidents (RTAs) on the physical health of children is well recognized, but their psychological consequences have only recently become a topic of research. While other traumatic experiences in childhood are well studied, this kind of trauma has been poorly investigated to date. Sampling and Methods: A prospective cohort study was conducted of 8- to 18-year-old children and adolescents who were involved in RTAs in a large urban area during a 6-month period. The children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 46 publications
0
46
0
1
Order By: Relevance
“…However, trait dissociation was related to questionnaireassessed PTSD severity on a multivariate basis, suggesting that trait and peritraumatic dissociation may each independently contribute to PTSD severity. These results contrast with findings in adults that trait dissociation fully accounts for the relationship between peritraumatic dissociation and PTSD Schafer, Barkmann, et al, 2006). Whereas Briere and colleagues' (2005) finding that trait dissociation accounted for the effects of peritraumatic dissociation was based on categorical PTSD diagnosis, another study with adults that used a continuous measure of PTSD severity (Hetzel & McCanne, 2005) found that peritraumatic dissociation was predictive independent of trait dissociation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, trait dissociation was related to questionnaireassessed PTSD severity on a multivariate basis, suggesting that trait and peritraumatic dissociation may each independently contribute to PTSD severity. These results contrast with findings in adults that trait dissociation fully accounts for the relationship between peritraumatic dissociation and PTSD Schafer, Barkmann, et al, 2006). Whereas Briere and colleagues' (2005) finding that trait dissociation accounted for the effects of peritraumatic dissociation was based on categorical PTSD diagnosis, another study with adults that used a continuous measure of PTSD severity (Hetzel & McCanne, 2005) found that peritraumatic dissociation was predictive independent of trait dissociation.…”
Section: Discussionmentioning
confidence: 66%
“…Witnessing domestic (Teicher et al, 2006) or community violence (McKelvey et al, 2011), and exposure to traumatic accidents (Schafer, Barkmann, Riedesser, & Schulte-Markwort, 2006) are associated with PTSD. Therefore, these additional exposures were included in this study.…”
mentioning
confidence: 99%
“…Only 2 studies focused exclusively on males (Marshall & Schell, 2002) or females (Engelhard, van den Hout, Kindt, Arntz, & Schouten, 2003). Only 1 of the selected studies focused on children (Schäfer, Barkmann, Riedesser, & Schulte-Markwort, 2006). Eight studies had a relatively small sample size of 86 or less.…”
Section: Resultsmentioning
confidence: 99%
“…No studies with positive outcomes (and only 1 study with negative outcomes, Schäfer et al, 2006) included children affected by a traumatic event. Only 1 positive (16.7%) and 3 negative (27.3%) studies included teenagers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation